Observed and simulated summer rainfall variability in southeastern South America - Díaz, Leandro Baltasar (2017)
The climate changes observed in the last decades have raised concern among policy and decision makers about the importance of improving the knowledge and prediction of climate. In particular, the Southeastern South America (SESA) is one of the few regions in the world which haveexperimented both large positive summer precipitation trends in mean and extremes during the 20th century. Furthermore, a precipitation increase is projected over the region for the current century. These changes pose a significant threat for many socio-economic sectors within this region.How anthropogenic forcings are combined with low frequency natural climate variability to modulate the regional rainfall variability and trends in SESA has not been explored in detail yet. Therefore, a deeperknowledge of decadal climate variability in the region is needed in order to project near term future changes with a larger degree of confidence. According to this, our goal is to understand the influence of the large-scale interannual variability of sea surface temperatures (SST) on austral summer rainfall in SESA in a global warming context and to evaluate if CMIP5 models are able to represent that influence properly.